Using phage display in autoimmunity research - Žager, Urška (Acta chimica slovenica, 2011)
Autoimmune diseases affect approximately 3% of the population and are a significant cause of morbidity and mortality. Therefore, they are the focus of vivid research aimed at the delineation of pathology, more efficient diagnosis and therapy. Phage display is a simple methodology markedly useful in studying protein-protein interactions which are the driving forces of (patho)physiological processes, including autoimmunity. The commercially available phage display peptide libraries allow the characterization and identification of antibody-antigen and receptor-ligand binding sites, thus providing basic insight into the pathological network. Through the phage display of antibodyćs, receptorćs or ligandćs protein domains it is possible to produce various self-specificities that have already been proven useful in the therapy of autoimmune diseases. Phage antibody display libraries are able to reprint the in vivo autoimmune response which significantly facilitates structural and functional analyses of auto-reactive antibodies and assessing their role in disease pathology. The aim of this review was an overview of the versatile applications of phage display technology to determine their potential advantages in studying autoimmune diseases and to critically categorize and analyze the usefulness of phage displays towards understanding pathology and towards development of improved diagnostic tools. Above all its focus was on targeted therapy.
Keywords: avto antigeni; avtoimunskebolezni; fagni zaslon; proteinske interakcije; protitelesa